Leiomyosarcoma of the duodenojejunal flexure. - Armand Ugon, César; Kamaid, Emil; Soto, José; Belloso, Rogelio; Iraola, M L (Cirugía del Uruguay, 1978)
The authors present a case of leiomyosarcoma of the duodenojejunal flexure, treated by resection and duodeno-jejunal anastomosis. Controls performed 15 months after operation revealed no signs of neoplastic activity